ANALISA KEBIJAKAN PUBLIK MENGENAI RANCANGAN UNDANG-UNDANG RAHASIA NEGARA - Nuraini, Siti (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2010)
The state secrets bill is very controversial on the one hand, proposed by the government because it is considered very important because it aims